THE STUDY OF CHEMICAL ASSEMBLY OF MACROMOLECULES IN POLYCONDENSATION OF DIFUNCTIONAL DIMETHYLSILANES - Е. М. Tarasova; A. V. Butuzov; A. A. Cherkasova; P. V. Ivanov (Тонкие химические технологии)
The article describes the results of a research on polycondensation “in situ” in the process of partial hydrolysis of dimethyldimetoxysilane and dimethyldiacetoxysilane as compared with similar data for the dimethyldichlorosilane and homofunctional condensation of dimethylsilandiol. The effect of the molar ratio of components on the composition of products of partial hydrolysis of the functional dimethylsilanes and dependence of the monomer conversion degree (Xm) vs. conversion of functional groups (Xf) are presented. It is shown that as the conversion of functional groups in composition products increases the share of dimethylcyclosiloxanes and reaches more than 99% (when Xf →1). It is found that among the monomers (CH3)2Si(OCH3)2 < (CH3)2Si(OCOCH3)2 ≈ (CH3)2SiCl2 the proportion of unit-to-unit assembling of oligomeric molecules, which are created by heterofunctional condensation of hydrolysis products and the proportion of organocyclosiloxanes are increasing. It is assumed that the heterophase process which is responsible for the lack of hydrolyzing agent due to its slow diffusion is the cause of the unit-to-unit assembling.